For whom the ball rolls ebook - Pilkey, Dav (Dog Man, 2019)
Petey learns what it means to do good in the seventh Dog Man book from worldwide bestselling author and artist Dav Pilkey. The Supa Buddies have been working hard to help Dog Man overcome his bad habits. But when his obsessions turn to fears, Dog Man finds himself the target of an all-new supervillain! Meanwhile, Petey the Cat has been released from jail and starts a new life with Li'l Petey. But when Petey's own father arrives, Petey must face his past and fight for who he loves. Dav Pilkey's wildly popular Dog Man series appeals to readers of all ages and explores universally positive themes, including empathy, kindness, persistence, and the importance of doing good.